Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I found this statement about rearrangement from analysis Lieb and Loss in chapter 3.

Suppose f, g are nonnegative functions in $L^2(\Bbb{R^n})$, then $||f^*-g^*||_2 \le||f-g||_2$

Where $f^*$ is the symmetric- decreasing rearrangement of $f$.

$f^*(x):=\int_0^{\infty} \chi_{\{|f|>t\}^*}(x)dt$.

I can see that it is true when $p=2$

but why it is true for $1 \le p \le \infty$, ie $||f^*-g^*||_p \le||f-g||_p$

share|cite|improve this question
up vote 1 down vote accepted

The case $p=\infty$ is easy: let $M=\|f-g\|_\infty$. Since $f\le g+M$, it follows that $f^*\le g^*+M$, and we are done.

For $1\le p<\infty$ the function $t\mapsto |t|^p$ is convex on $\mathbb R$, which means that we can use Theorem 3.5 on the very same page of the book you are reading.

3.5 Theorem (nonexpansivity of rearrangement). Let $J:\mathbb R\to\mathbb R$ be a nonnegative convex function such that $J(0)=0$. Let $f$ and $g$ be nonnegative functions on $\mathbb R^n$, vanishing at infinity. Then $$\int_{\mathbb R^n} J(f^*-g^*)\le \int_{\mathbb R^n} J(f-g)\tag{1}$$ If we also assume that $J$ is strictly convex, that $f=f^*$, and that $f$ is strictly decreasing [in radial direction], then equality in (1) implies that $g=g^*$.

I suspect you asked this question because of the sentence "the obvious generalization is $\|f^*-g^*\|_p \le \|f-g\|_p$". I guess the authors did not mean to say "this generalization is obviously true", but rather "obviously, this is a generalization".

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.